History of Administrative Documents in Vietnam - From the 10th Century to present - Hoc, Do Van (Journal of Ecohumanism, 2024)
The formation and transformation of the administrative document system in Vietnam throughout history have always been closely associated with the changes and development of the country, holding a very important position. The historical context, content, significance, characteristics, and experiences of this process are of great significance not only in Vietnam but also on an international scale. The formation and transformation of the administrative document system during the feudal period in Vietnam were influenced and impacted by Chinese characters and the administrative document systems of Chinese feudal dynasties. The formation and transformation of administrative documents based on the National language script (Quốc ngữ) were influenced and impacted by the Latin script system from many centuries ago and the administrative document systems of France and Western countries during the modern period. The administrative document system in Vietnam throughout history is deeply imbued with Vietnamese identity and is based on the influence, exchange, and mutual impact with the cultures of China, the French Republic, and many countries around the world. This foundation provides significant similarity and advantages, helping Vietnam integrate into the world and cooperate with other countries for mutual development.